Physiological and biochemical mechanisms preventing Cd-toxicity in the hyperaccumulator Atriplex halimus L. - Mesnoua, Mohammed; Mateos-Naranjo, Enrique; Barcia-Piedras, José María; Pérez-Romero, Jesús Alberto; Lotmani, Brahim; Redondo-Gomez, Susana (Plant Physiology and Biochemistry, 2016)
The xero-halophyte Atriplex halimus L., recently described as Cd-hyperaccumulator, was examined to determine Cd toxicity threshold and the physiological mechanisms involved in Cd tolerance. An experiment was conducted to investigate the effect of cadmium from 0 to 1350 mM on chlorophyll fluorescence parameters, gas exchange, photosynthetic pigment concentrations and antioxidative enzyme activities of A. halimus. Cadmium, calcium, iron, manganese, magnesium, potassium, phosphorous, sodium and zinc concentrations were also analyzed. Plants of A. halimus were not able to survive at 1350 mM Cd and the upper tolerance limit was recorded at 650 mM Cd; although chlorosis was observed from 200 mM Cd. Cadmium accumulation increased with increase in Cd supply, reaching maxima of 0.77 and 4.65 mg g 1 dry weight in shoots and roots, respectively, at 650 mM Cd. Dry mass, shoot length, specific leaf area, relative growth rate, net photosynthetic rate, stomatal conductance, pigments contents and chlorophyll fluorescence were significantly reduced by increasing Cd concentration. However, the activities of superoxide dismutase (SOD; EC1.15.1.1), catalase (CAT; EC1.11.1.6) and guaiacol peroxidase (GPx; EC1.11.1.7) were significantly induced by Cd. Exposures to Cd caused also a significant decrease in P contents in roots, Mg and Mn contents in shoots and Fe and K contents in roots and shoots and had no effect on Ca, Na and Zn contents. The tolerance of A. halimus to Cd stress might be related with its capacity to avoid the translocation of great amounts of Cd in its aboveground tissues and higher activities of enzymatic antioxidants in the leaf.
Keywords: Antioxidative enzyme activity, Fluorescence, Growth parameters, Mineral nutrients, Photoinhibition, Photosynthesis.